Non-metallic inclusions in 17-4PH stainless steel parts produced by selective laser melting. (15th February 2018) - Sun, Yu; Hebert, Rainer J.; Aindow, Mark
Abstract: The character, morphology and distribution of inclusions has been studied in additively manufactured 17-4PH stainless steel parts produced from gas-atomized powder by selective laser melting. A combination of advanced electron microscopy techniques has been used to show that such parts contain oxide inclusions ranging from a few nm to tens of μm across. The coarser inclusions have morphologies that mimic the oxides which accumulate between melt tracks at the build surface, suggesting that these inclusions are incorporated into the build during deposition of subsequent layers. Such features could have deleterious anisotropic effects upon the fatigue and fracture resistance of the built parts. The finer inclusions are equi-axed, reside preferentially at grain boundaries, and could inhibit grain growth during processing via Zener pinning effects. The chemistries of the inclusions include elements such as Al that are not part of the alloy specification. This indicates that the inclusions are exogenous defects that are entrained in the melt during gas atomization due to interactions with the crucible or nozzle materials. Examples of encapsulated oxide material in the powder feedstock support this explanation. These observations highlight the need for careful control of powder pedigree when using additive manufacturing for critical structural components. Graphical abstract: Image 1 Highlights: Inclusions consisting of amorphous oxides of silicon and aluminum are observed in additively manufactured 17-4 PH samples. The largest inclusions are many microns across with characteristic shapes, and contain crystalline alloy nanoparticles. Oxide phases with similar morphologies are found between the tracks at the build surface of the samples. The origin of the oxides is shown to be entrained refractory material within the powder feedstock. These observations highlight the importance of powder pedigree in metal additive manufacturing.